The role of humic acid from various composts in improving degraded soil fertility and maize yield - Niken R Wandansari; Soemarno Soemarno; Retno Suntari; Syahrul Kurniawan (Brawijaya University, 2023)
Humic acids play a crucial role in ion exchange and metal ion complexes; therefore, they are potentially useful in improving soil fertility and crop yield. This study aimed to explore the role of humic acid (HA) from various composts in improving degraded soil fertility and maize yield. A field experiment was conducted on Inceptisols having low soil organic carbon, nitrogen and available phosphorus contents. Eight treatments of HA formulas and one control were arranged in a randomized block design with three replications. The HA formulas used were combinations of two doses of HA (0.15 and 0.20% of soil on w w-1 base) and four types of HA (HA extracted from bagasse compost, HA extracted from water hyacinth compost, HA extracted from market waste compost, and commercial HA). The results showed that the HA application increased 16-97% of soil organic carbon, total nitrogen, available phosphorus, exchangeable potassium and calcium compared to the control. The formula of commercial HA at 0.15% was the best treatment for inhibiting soil fertility degradation in agricultural land. The best maize yield of 15.13 t ha-1 and starch content of 63.54% was obtained from the application of commercial HA at 0.20%.